Descrição anatômica com avaliação ultrassonográfica e histológica de testículos de Leontopithecus chrysomelas (Kuhl, 1820), Callitrichidae, Primates - Lundstedt, Michelle Nogueira (Universidade Federal de São Carlos, 2025)
Habitat fragmentation limits the movement and mating of Leontopithecus chrysomelas, reducing genetic variability and increasing the risk of inbreeding. In Rio de Janeiro State, individuals accidentally introduced into an area of the Atlantic Forest pose a threat to local wildlife and public health due to the risk of hybridization and transmission of unknown pathogens. This research conducted an anatomical study of the testes of L. chrysomelas using ultrasound and histological examinations of the different stages of maturation, identifying the spermatogenic lineage present in the germinal epithelium of the seminiferous tubules. The result will be a morphological description of the testes and epididymis of this species, and the knowledge generated may support comparative studies of the reproductive ecology of neotropical primates, as well as aid in the development of techniques such as cryopreservation of testicular tissue.
Anatomical description with ultrasonographic and histological evaluation of the testes of Leontopithecus chrysomelas (Kuhl, 1820), Callitrichidae, Primates
Keywords: Mico-leão-de-cara-dourada; Conservação; Reprodução; Anatomia; Golden-headed lion tamarin; Conservation; Reproduction; Anatomy; CIENCIAS BIOLOGICAS::MORFOLOGIA::ANATOMIA::ANATOMIA ANIMAL; CIENCIAS AGRARIAS::MEDICINA VETERINARIA; 15. Vida Terrestre; 3. Saúde e Bem-Estar